Intraoperative oximetry of hollow organs in case of gunshot injuries of the abdomen - I. V. Sobko (Сучасні медичні технології)
The aim of the study is to analyze the application of intraoperative oximetry for assessing the viability of hollow organ segments during the implementation of Damage Control Surgery (DCS) in patients with gunshot abdominal injuries.